In silico identification of candidate miRNA-encoded Peptides in four Fabaceae species. (April 2022) - de Araújo, Paula Machado; Grativol, Clícia
Abstract: MicroRNAs (miRNAs) are one of the main regulators of gene expression. Recent studies have demonstrated that primary transcripts of miRNAs (pri-miRNAs) encode regulatory peptides, called miRNA-encoded peptides (miPEPs), capable of enhancing the expression of their associated miRNAs in plants. In this work, we aimed to computationally identify miPEPs produced by small open reading frames (ORFs) in pri-miRNAs from four species of Fabaceae. Five families of miRNAs were investigated, based on their role in plant-microorganism interaction. We used the miR171 family as a training dataset centered on the information about mtr-miPEP171b and vvi-miPEP171d already described. From the sequences of the pri-miRNAs and the genomic regions where they were located, ORFs encoding putative miPEPs were predicted. The 5′-most ORFs encoding peptides on pri-miRNAs were aligned and the amino acids conservation was observed. In total, 81 sequences of potential miPEPs were identified. We found conserved miPEPs inside pri-miRNAs from soybean and between soybean, common bean, and cowpea. Besides, our results showed few conserved miPEPs among isoforms of the same miRNA and no conservation among different miRNA families, which indicate the possible specificity of miPEPs in relation to their corresponding miRNAs. Our findings contribute to the understanding of miPEPs features in plants and provide the basis for studies aiming the biotechnological use of miPEPs in leguminous species. Graphical Abstract: ga1 Highlights: Evaluate the criteria for computational miPEP prediction using a training dataset. In silico analysis allowed the identification of 81 potential miPEPs in legumes. The 5′-most ORFs encoding peptides on pri-miRNAs showed conservation among legumes. Few conserved miPEPs among miRNA isoforms were found in leguminous species.